المؤسسات السياحية و دورها في ترويج المنتج السياحي بولاية سوق أهراس - أمل رفاس; آسيا عنتر (My University, 2022)
This study aimed to determine the role of tourism institutions in the Application of promotional mix techniques, in order to promote the tourism product in the state of Souk Ahras, where tourism institutions were relied upon to study efforts to promote the tourism product in the state. In this study, it was relied on the descriptive analytical method, for the theoretical study and the case study method in the applied study. Also, for the purpose of collecting information, a questionnaire was designed and distributed to a sample of 15 tourism agencies. To achieve the objectives of research and data analysis, the statistical system was relied on. This study concluded that there is a statistically significant impact on the role of the tourism agency in promoting the tourism product in the state of Souk Ahras, through websites, publishing pictures and videos, and participating in tourism demonstrations and festivals. Based on these results, a set of suggestions were presented, which contribute to the application of tourism institutions in the state of Souk Ahras, on the techniques of the promotional mix of promoting the tourism product in the state. ........................................... هدفت هذه الدراسة الى تحديد دور المؤسسات السياحية في تطبيق تقنيات المزيج الترويجي، من أجل الترويج المنتج السياحي بولاية سوق اهراس، حيث تم الاعتماد على المؤسسات السياحية لدراسة الجهود من اجل الترويج للمنتج السياحي بالولاية. وقد تم الاعتماد في هذه الدراسة على المنهج الوصفي التحليلي، للدراسة النظرية ومنهج دراسة الحالة في الدراسة التطبيقية كما انه لغرض جمع المعلومات، تم تصميم استبيان تم توزيعه على عينة مكونة من 15 وكالة سياحية ولتحقيق اهداف البحث وتحليل البيانات،تم الاعتماد على النظام الاحصائي. وقد خلصت هذه الدراسة إلى وجود أثر ذو دلالة احصائية ذو دلالة احصائية، بدور الوكالة السياحية في ترويج المنتج السياحي في ولاية سوق اهراس، من خلال المواقع الإلكترونية نشر الصور والفيديوىات والمشاركة في التظاهرات والمهرجانات السياحية. وبناءا على هذه النتائج تم تقديم مجموعة من الاقتراحات، تساهم في تطبيق المؤسسات السياحية بولاية سوق اهراس، على تقنيات المزيج الترويجي من الترويج المنتج السياحي بالولاية